High-intensity interval training using electrical stimulation ameliorates muscle fatigue in chronic kidney disease-related cachexia by restoring mitochondrial respiratory dysfunction - Fusagawa, Hiroyori; Sato, Tatsuya; Yamada, Takashi; Naito, Azuma; Tokuda, Nao; Yamauchi, Nao; Ichise, Nobutoshi; Ogawa, Toshifumi; Karaushi, Takuro; Teramoto, Atsushi; Tohse, Noritsugu (Frontiers in Physiology, 2024)
Exercise, especially high-intensity interval training (HIIT), can increase mitochondrial respiratory capacity and enhance muscular endurance, but its systemic burden makes it difficult to safely and continuously prescribe for patients with chronic kidney disease (CKD)-related cachexia who are in poor general condition. In this study, we examined whether HIIT using electrical stimulation (ES), which does not require whole-body exercise, improves muscle endurance in the skeletal muscle of 5/6 nephrectomized rats, a widely used animal model for CKD-related cachexia.Male Wistar rats (10 weeks old) were randomly assigned to a group of shamoperated (Sham) rats and a group of 5/6 nephrectomy (Nx) rats. HIIT was performed on plantar flexor muscles in vivo with supramaximal ES every other day for 4 weeks to assess muscle endurance, myosin heavy-chain isoforms, and mitochondrial respiratory function in Nx rats. A single session was also performed to identify upstream signaling pathways altered by HIIT using ES.In the non-trained plantar flexor muscles from Nx rats, the muscle endurance was significantly lower than that in plantar flexor muscles from Sham rats. The proportion of myosin heavy chain IIa/x, mitochondrial content, mitochondrial respiratory capacity, and formation of mitochondrial respiratory supercomplexes in the plantaris muscle were also significantly decreased in the non-trained plantar flexor muscles from Nx rats than compared to those in plantar flexor muscles from Sham rats.Treatment with HIIT using ES for Nx rats significantly improved these molecular and functional changes to the same degrees as those in Sham rats. Furthermore, a single session of HIIT with ES significantly increased the phosphorylation levels of AMP-activated protein kinase (AMPK) and p38 mitogenactivated protein kinase (MAPK), pathways that are essential for mitochondrial activation signaling by exercise, in the plantar muscles of both Nx and Sham rats.The findings suggest that HIIT using ES ameliorates muscle fatigue in Nx rats via restoration of mitochondrial respiratory dysfunction with activation of AMPK and p38 MAPK signaling.Our ES-based HIIT protocol can be performed without placing a burden on the whole body and be a promising intervention that is implemented even in conditions of reduced general performance status such as CKD-related cachexia.